Interspecific plant interaction structures the microbiomes of poplar-soil interface to alter nutrient cycling and utilization - Yimin You; Liran Wang; Xiaoting Liu; Xuelai Wang; Luping Jiang; Changjun Ding; Weina Wang; Dawei Zhang; Xiyang Zhao (Microbiology Spectrum, 2024)
ABSTRACTTerrestrial plants can influence the growth and health of adjacent plants through interspecific interaction. Here, the mechanisms of interspecific plant interaction on microbial function and nutrient utilization in the plant-soil interface (non-rhizosphere soil, rhizosphere soil, and root) were studied by soybean- and potato-poplar intercropping. First, metagenomics showed that soybean- and potato-poplar intercropping influenced the composition and co-occurrence networks of microbial communities in different ecological niches, with higher stability of the microbial community in soybean intercropping. Second, the gene abundance related to carbon metabolism, nitrogen cycling, phosphorus cycling, and sulfur cycling was increased at the poplar-soil interface in soybean intercropping. Moreover, soybean intercropping increased soil nutrient content and enzymatic activity. It showed higher metabolic potential in nutrient metabolism and transportation. Third, functional microorganisms that influenced nutrient cycling and transportation in different intercropping have been identified, namely Acidobacteria, Sphingomonas, Gemmatimonadaceae, Alphaproteobacteria, and Bradyrhizobium. Therefore, intercropping can construct microbial communities to alter metabolic functions and improve nutrient cycling and absorption. Interspecific plant interactions to influence the microbiome were revealed, opening up a new way for the precise regulation of plant microbiome.IMPORTANCEPoplar has the characteristics of wide distribution, strong adaptability, and fast growth, which is an ideal tree species for timber forest. In this study, metagenomics and elemental analysis were used to comprehensively reveal the effects of interspecific plant interactions on microbial communities and functions in different ecological niches. It can provide a theoretical basis for the development and application of the precise management model in poplar.